Education on the Introduction of Livestock and Animal-Derived Food Products for Improving Students’ Knowledge in Elementary School - Yayuk Kurnia Risna; Chairul Fadli; Koji Al Adam; Nanda Fatmala (Universitas Lambung Mangkurat, 2024)
The community service aimed to enhance students’ knowledge of various livestock and the importance of animal-derived food products as the foundation for a healthy and nutritious life. One of the potentials for children's intelligence comes from consuming healthy food products. Activities were carried out using exposure and evaluation methods through pre-test and post-test. The activity results showed increased students' knowledge, with the average pre-test score being 50.74 and the average post-test score after the material presentation being 83.70. During the activity, students were seen as enthusiastic about the material presented. In conclusion, this activity improved knowledge regarding the recognition of various livestock and animal-derived food products. Students were able to enhance their understanding of various ruminant and poultry livestock based on their characteristics and names. Additionally, students better understood the sources of healthy and nutritious animal protein food products.